(untitled) (Ibrahim Cardiac Medical Journal, 2024)
Background & objective: Urinary tract infections (UTIs) are a common cause of febrile illness in young children. Due to the absence of overt clinical features in young children, appropriate collection of urine samples, and basic diagnostic tests at first-level health facilities in our country, UTIs are not generally reported as a cause of childhood morbidity. Due to a lack of studies on the epidemiology, risk factors, diagnosis, treatment, prognosis, and prevention of UTI in children in our country, the exact picture of this disease is yet unknown. This study is intended to identify the risk factors of UTI in children in our country. Methods: The present cross-sectional study was carried out in the Department of Pediatrics (both indoor and outdoor) of Bangabandhu Sheikh Mujib Medical University, BIRDEM, and Dhaka Medical College Hospital over a period of 1½ years from January 2015 to June 2016. A total of 201 children with signs and symptoms suspected of having urinary tract infections were subjected to urine culture; of them, 98 had definitive UTI and the rest 103 had no UTI or possible UTI. Several factors such as circumcisional status, constipation, encopresis, previous hospital admission, and premature birth were investigated whether they had any role in contributing to the development of UTI. Result: The children with UTIs were relatively young compared to those without UTIs. However, the age incidence of UTI was found to differ by sex. About one-third of UTI cases in boys were found in the first year of life, one-third between 2nd to 3rd year of life, and the rest one-third in 3rd year onwards. However, the peak age incidence in girls was observed to be 3rd year and onwards. In terms of clinical presentation, fever, and anorexia were more or less common (52% and 43.7% respectively), abdominal pain was less common (18%), and irritability and vomiting were seldom observed. The presence of constipation was significantly associated with UTI in children (p = 0.001). Encopresis was considerably higher in the UTI group than in the non-UTI group (p = 0.169). Conclusion: Children with UTI usually present with fever with or without dysuria, frequency, anorexia, and abdominal or loin pain. While boys more often acquire the disease in their infancy, girls usually present with the problem from 3 years during their toilet training. Thus, the children presented with unexplained febrile illness or any other signs and symptoms should be suggested for a urine culture to find the clue of febrile illness. Identification of risk factors of UTI will go a long way in preventing the same illness in the future. Ibrahim Card Med J 2023; 13 (1&2): 60-65